Piloting Health Text Messages for Rural Low-Income Mothers: Effects of Source Similarity and Simple Action Steps. Issue 5 (September 2016) - Aldoory, Linda; Yaros, Ronald A.; Prado, Antonio A.; Roberts, Erica; Briones, Rowena L.
Approximately 85% of people living in rural settings own a cell phone, and of those, 76% send or receive text messages. Thus, text messaging may be an effective way to reach rural low-income mothers with important information and resources that will improve their health and well-being. This exploratory study examined the utility of using text messaging for disseminating health information to rural low-income mothers. Researchers tested messages that were personalized and sent from a source similar to participants, a mom named Ms. Peg. Ms. Peg sent text messages about physical activity, oral health, nutrition, and health insurance—facts and tips that addressed barriers and lifestyles in rural low-income contexts—over a 4-week period. Participants completed a prequestionnaire assessing healthy behaviors, text message use and preference, and demographic information. Participants then received two text messages for 4 weeks. Findings indicated that participants were satisfied receiving information through text messages, with half finding it "easy" and "convenient." The majority reported being highly motivated by the messages, and for 41% the messages were associated with self-efficacy and intention to act. Close to half of the participants found the use of personalization effective and perceived the messages as "relatable."